WAHANA SISTEM KENDALI TERSEBAR DALAM JARINGAN SENSOR NIRKABEL ARSITEKTUR TITIK TUNGGAL - Ontowirjo, Abdul Haris Junus (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
In this paper described a simple model of control system include with time delay according to communication network. Time delay in wireless sensor network also explained. As an embedded system, each sensor point in wireless sensor network have operating system with schedulling strategy and certain programming paradigm also communication system with protocol. This two aspects had been analyzed according its contribution to time delay. Hardware implementation was designed and related with time delay characteristic and model. The hardware design using single point architecture could be possibly as starting point for developing distributed control strategies in wireless sensor network. Keywords: wireless sensor network, time delay, distributed control, sensor point, actuator point